2013
DOI: 10.1080/15438627.2012.757229
|View full text |Cite
|
Sign up to set email alerts
|

Injury Type and Incidence Among Elite Level Curlers During World Championship Competition

Abstract: Our objective was to investigate the incidence of musculoskeletal injuries sustained by elite level curling athletes during international competition. This study was conducted during the 2008 World Men's Curling Championships. All registered athletes and the tournament medical team were given report forms for documenting injuries that occurred during the tournament. Report form information included demographics, area injured, types of injuries sustained, and curling-specific aggravating conditions. During the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
9
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 6 publications
1
9
0
1
Order By: Relevance
“…The third paper claimed to find results similar to those reported by Berry et al 2. Beere et al 3 reported 216 injuries over a 10-year period in high-performance curlers.…”
Section: Introductionmentioning
confidence: 57%
See 1 more Smart Citation
“…The third paper claimed to find results similar to those reported by Berry et al 2. Beere et al 3 reported 216 injuries over a 10-year period in high-performance curlers.…”
Section: Introductionmentioning
confidence: 57%
“…A retrospective study carried out in the USA analysed injury patterns among competitive curlers, showing that over 54% of injuries were to the knee 1. Berry et al 2 surveyed participants at the 2008 World Men's Curling Championships and reported five musculoskeletal injuries, all of which were pain on curling-related movements, were sustained throughout the championships.…”
Section: Introductionmentioning
confidence: 99%
“…4 At another men's championship, acute injuries occurred at a self-reported rate of 3.5 per 1000 AEs. 6 At the 2010 Winter Olympics, the acute injury rate requiring medical attention was 2.5 per 1000 AEs; the two acute injuries happened to men while the women's bracket reported no injuries. 7 Most of the injuries reported were sprains to the knee, back and shoulder; none specifically reported head injuries.…”
Section: Introductionmentioning
confidence: 99%
“…Une étude axée sur les deux championnats nationaux a révélé que le taux autodéclaré de blessures graves entraînant une « perte de temps », ce qui caractérise l'exposition de l'athlète, était de 2 à 2,3 par 1 000 parties jouées 4 . Lors d'un autre championnat masculin, le taux autodéclaré de blessures graves a été de 3,5 par 1 000 athlètes exposés 6 . Lors des Jeux olympiques d'hiver de 2010, le taux de blessures ayant néces-sité des soins médicaux était de 2,5 par 1 000 athlètes exposés, les 2 cas recensés étant survenus chez les hommes et aucun incident du même genre n'ayant été signalé chez les femmes 7 .…”
Section: Introductionunclassified